Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1007/s00239-012-9504-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Nucleotide Diversity Across North American and European Populus Species

Abstract: Nucleotide polymorphisms in two North American balsam poplars (Populus trichocarpa Torr. & Gray and P. balsamifera L.; section Tacamahaca), and one Eurasian aspen (P. tremula L.; section Populus) were compared using nine loci involved in defense, stress response, photoperiodism, freezing tolerance, and housekeeping. Nucleotide diversity varied among species and was highest for P. tremula (θ(w) = 0.005, π(T) = 0.007) as compared to P. balsamifera (θ(w) = 0.004, π(T) = 0.005) or P. trichocarpa (θ(w) = 0.002, π(T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 78 publications
1
27
1
Order By: Relevance
“…The rapid decay of LD in this population also means that high marker density will be required for association analysis to avoid missing possible significant markers or functional variations. However, the decline of LD with distance within PtoCesA3 extended over longer distances than the LD decline observed for candidate genes in several related species of Populus, where a rapid decay of LD occurs within a few hundred base pairs (Ingvarsson 2005(Ingvarsson , 2008Wegrzyn et al 2010;Ismail et al 2012). Previous studies conducted by Olson et al (2010) and Guerra et al (2013) reported that LD decayed over significantly longer distances in P. balsamifera and P. nigra genes.…”
Section: Nucleotide Diversity and Linkage Disequilibrium In Ptocesa3mentioning
confidence: 72%
“…The rapid decay of LD in this population also means that high marker density will be required for association analysis to avoid missing possible significant markers or functional variations. However, the decline of LD with distance within PtoCesA3 extended over longer distances than the LD decline observed for candidate genes in several related species of Populus, where a rapid decay of LD occurs within a few hundred base pairs (Ingvarsson 2005(Ingvarsson , 2008Wegrzyn et al 2010;Ismail et al 2012). Previous studies conducted by Olson et al (2010) and Guerra et al (2013) reported that LD decayed over significantly longer distances in P. balsamifera and P. nigra genes.…”
Section: Nucleotide Diversity and Linkage Disequilibrium In Ptocesa3mentioning
confidence: 72%
“…Much higher overall nucleotide diversity levels in a conifer were uncovered for P. taeda (π = 0.00398; [86]). Among the studied poplars, interestingly, the European species, P. tremula, showed the highest nucleotide diversity (π = 0.007 [87] or even π = 0.0111 [88], dependent on the surveyed genes), but differences in diversity were also consistent with its different and complex demographic history. However, nucleotide diversity is best interpreted on a gene-by-gene basis, as population history and selection affect these mutation rates more specifically [40,89].…”
Section: Forest Tree Population Diversitymentioning
confidence: 81%
“…Populus (Ismail et al, 2012), Pinus (González Martinez et al, 2006;Wachowiak et al, 2011) and Quercus (Derory et al, 2012).…”
Section: Resultsmentioning
confidence: 99%